Subversion of the Established Representation of Judeo-Christian Teachings in Philip Pullman’s His Dark Materials - Ms. Jyoti Gour and Dr Sarla Singla (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Pullman has used various strategies throughout the trilogy to introduce these, somewhat dogmatic, perceptions; rewritten in such a way that they cast new light upon the matters they are related to or are presented in an unaltered way. Pullman defines this utterly religious concept giving it a political, as well as a spiritual connotation, as this is ripe for interpretation and play. In Catholicism, death is a new beginning of next life; one starts its journey to heaven where boundless joy awaits only for them who are worthy and on the other hand interminable suffering for those who are sinful. Pullman’s real issue is not religious belief itself, but religious power, and how it attempts to undermine personal freedom and understanding but even then, as religion is in the centre of Pullman’s trilogy so, it is necessary to understand the difference between theistic and atheistic approaches for they seem as contrary to each other but here they are compared with each other. Pullman has presented Religion as a ruthless, joyless, implacable power, standing on the edifice of a lie to suppress the freedom of individuals and to crumple their creativity and imagination. It is mentioned repeatedly how the Church tries to keep people in the unawareness whereas the rebels are trying to enforce freedom of thought.